Modélisation de l'érosion hydrique à l’échelle du bassin versant du Mhaydssé. Békaa-Liban - Hussein El Hage Hassan; Laurence Charbel; Laurent Touchart (VertigO)
The high plains of Lebanon are subject to water erosion which tends to strip its soils and threaten its agricultural activities. The combined effect of anthropogenic actions (cultural management, deforestation, overgrazing) and natural factors (climatic aggressiveness, steep slopes, soil), weakens the soil and threatens agricultural parcels by depositing sediments. Mhaydssé is a village concerned by this problem and its representative of the natural and anthropogenic conditions of the Békaa’s southeast. The study uses GIS and the Universal Earth Loss Equation (USLE). To replace the intensity of precipitation, the aggressiveness index was calculated from the equation of Renard and Freimund. Five soil types were sampled, for which the soil granulometry was analyzed in five classes. The topography (slope), the vegetation cover and the anti-erosion practices are the other factors that have been quantified. Of the 1800 hectares of the study area, the average loss of land is 46 t / ha / year. This high value comes from a high spatial heterogeneity. The barren slopes are subject to rates above 300 t /ha /yr, while the bottom of the plain is practically untouched. Large spatial differences over small distances confirm the thoroughness of an accurate analysis of soil texture.